If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 = x + 19 Reorder the terms: -27 = 19 + x Solving -27 = 19 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -27 + -1x = 19 + x + -1x Combine like terms: x + -1x = 0 -27 + -1x = 19 + 0 -27 + -1x = 19 Add '27' to each side of the equation. -27 + 27 + -1x = 19 + 27 Combine like terms: -27 + 27 = 0 0 + -1x = 19 + 27 -1x = 19 + 27 Combine like terms: 19 + 27 = 46 -1x = 46 Divide each side by '-1'. x = -46 Simplifying x = -46
| -2(5-3m)= | | 3(7)/3= | | 3z-(10)=1 | | log(12x^4)-log(2x^3)=2 | | 4(5+7b)+6b=-252 | | cos(x)=-0.5 | | 5ln(x-11)-3=7 | | 8x^2-6x-3=0 | | 3(5-15)=m-5 | | 3x+25=12x+83 | | 3a-1(-1)=-5 | | 4(3y-3)-2y=-9 | | 4v+-3v-4=13 | | 6x^2-2x^3-4x=0 | | 2k-16-10k=-2k | | 207-7x=38x+22 | | -12-3+9= | | 6(x+4)-(2x-8)= | | 5-(-8)=x | | y^2-5y-3=0 | | 5(d-6)+6= | | 2m^3-5m^2-12m=0 | | (2x-3)+(x^2-4x)=180 | | 5x^2+3x-16=32-31x | | -3u+8=14 | | c-(-2)=68 | | 3y+4=-20 | | 56=4y | | 50=(x+10)x | | [(5*6-4)-20]= | | 2a+10=26 | | c+-52=68 |